Geographical Assessment of the Natural Environment at Al-Huwaizah Marsh, Eastern of Misan Governorate (Iraq) - Bashar F. Maaroof 1, Mohammed A. Al-Musawi 2, Hashim H. Kareem 2, Raheem H. Al-Abdan 3, Hanan S. Obaid 4, Ban AL- Hasani 5, Mawada Abdellatif 5, Iacopo Carnacina 5 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
In this article, Al-Huwaizah Marsh, one of the biggest wetlands in southern Iraq, has been studied. The spatial analysis approach was used to study the spatial relationships between the elements of the natural environment on the one hand, and their relationship to the distribution of organisms in Al-Huwaizah Marsh on the other hand. A geographic information system (GIS) was established and fed with the data contained in the topographical, geological, pedological, and hydrological maps issued by the various Iraqi institutions. The study hypothesis indicated that the abiotic elements of the ecosystem (location, surface, geological structure, climate, and soil) played a direct role in the geographical distribution of biotic elements (animals and plants) of Al-Huwaizah Marsh. Al-Huwaizah Marsh is a natural depression that collects water during floods and is distinguished by providing an ideal environment for different species of birds, fish, mammals, and plants to live. The four most significant waterbodies of Al-Huwaizah Marsh are Al-Edhaim, Umm Al-Na’aj, Al-Sanaf, and Al-Jakka.